Zoogloea ramigera Itzigsohn, identification and description1 - CRABTREE, K.; MCCOY, ELIZABETH (International Journal of Systematic and Evolutionary Microbiology, 1967)
SUMMARY The problem of identity and nomenclature of Zoogloea ramigera Itzigsohn has been presented. A new strain I-16-M has been described in terms of modern systematic bacteriology and it is proposed for designation as the neotype strain. An Opinion as to validity of the generic name Zoogloea Cohn is requested, and, if found invalid, designation of Zoogloea Itzigsohn as a nomen conservandum.